Improving Social Studies Learning Media Literacy in Elementary School Students Through Virtual Tour Media of Lebak Local Products - Ginanjar, Ajeng; Abdulkarim, Aim; Komalasari, Kokom; Wiyanarti, Erlina (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to develop learning media based on virtual tours of local products in Lebak Regency and measure its effectiveness in improving media literacy and understanding of social studies learning concepts of elementary school students. The method used was an experiment with a pretest-posttest control group design, involving 64 grade IV students who were divided into two groups: an experimental group that used virtual tour media and a control group that used conventional learning methods. The virtual tour media is designed to introduce Lebak's local products, such as handicrafts, typical foods, and the production process, so that students can learn interactively without distance and time restrictions. Data was obtained through media literacy tests, social studies comprehension tests, observation sheets, and student response questionnaires. Data analysis was carried out using parametric statistical tests, including normality tests, homogeneity, independent sample t-tests, and normalized gain analysis (N-Gain). The results showed that the experimental group experienced a significant increase in media literacy and social studies comprehension compared to the control group. In addition, students in the experimental group responded positively to the use of virtual tour media. The virtual tour media has proven to be effective not only to increase students' understanding of the learning material, but also to strengthen their appreciation of local wisdom. The recommendation for further research is the development of similar media that can be implemented in other subjects with different local contexts.